2016
DOI: 10.1016/j.schres.2015.12.011
|View full text |Cite
|
Sign up to set email alerts
|

The interactive effects of negative symptoms and social role functioning on suicide ideation in individuals with schizophrenia

Abstract: Findings regarding the protective effect of social role functioning on suicide ideation in individuals with schizophrenia have been mixed. One reason for such inconsistencies in the literature may be that individuals with prominent negative symptoms of schizophrenia may not experience a desire for social closeness, and therefore social role functioning may not influence suicide risk in these individuals. The aim of this study was to examine the moderating effects of self-reported desire for social closeness an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 37 publications
(53 reference statements)
2
11
0
Order By: Relevance
“…Jahn and colleagues [35] studied 162 patients affected by schizophrenia or schizoaffective disorder and found that motivation and pleasure scores as rated by the Clinical Assessment Interview for negative symptoms (CAINS) were not directly associated with recent suicidal ideation. However, motivation and pleasure-related scores moderated the relationship between social role functioning and suicide ideation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jahn and colleagues [35] studied 162 patients affected by schizophrenia or schizoaffective disorder and found that motivation and pleasure scores as rated by the Clinical Assessment Interview for negative symptoms (CAINS) were not directly associated with recent suicidal ideation. However, motivation and pleasure-related scores moderated the relationship between social role functioning and suicide ideation.…”
Section: Resultsmentioning
confidence: 99%
“…The most consistent association was found for patients with affective disorders (7 of 7 studies reported a significant positive association) and for patients with PTSD (3 of 3 studies reported a positive association). For the two studies of patients with schizophrenia, one found no association (Jahn et al [35]) and the other found a negative association (Loas et al [18]). For patients who had attempted suicide (and who were undiagnosed), one study found a positive association [39], one a positive association but only for depressed attempters [33], and one found a negative association [13].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some studies reported that negative symptoms (e.g. diminished emotional expression) were inversely related to suicide risk (Fenton et al 1997; Bertelsen et al 2007; Chang et al 2014); others found that negative symptoms significantly conferred risk (Havaki-Kontaxaki et al 1994; Steblaj et al 2007), with some reporting a non-significant relationship (Nordentoft et al 2002; Hawton et al 2005; Jahn et al 2016). Similar debates exist regarding positive symptoms such as delusions and hallucinations (Kelleher et al 2012; Chang et al 2014; DeVylder et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In the broader literature, it is sufficiently documented that one important and common risk factor for death by suicide among individuals with schizophrenia is suicide ideation, which often serves as an outcome in studies of suicide risk (Fulginiti & Brekke, ; Jahn et al., ; Kasckow et al., ) and as a viable and recommended target for suicide prevention efforts among individuals with schizophrenia (Fialko et al., ; Fulginiti & Brekke, ). Many well‐regarded empirical studies have reported that various illness‐related risk factors, including a history of suicide attempts, depression, hopelessness, lower self‐esteem, and poorer QoL, may predict suicide ideation and attempts in schizophrenia (Hor & Taylor, ; Popovic et al., ).…”
Section: Insight Paradox In Schizophreniamentioning
confidence: 99%